THE EFFECT OF COMBINATION OF PEARLITOL® 400DC AND CROSCARMELLOSE SODIUM ON THE PHYSICAL PROPERTIES OF FAST DISINTEGRATING TABLET HIDROKLOROTIAZID - Margareta Anindya Christianti; T.N. Saifullah Sulaiman (Faculty of Pharmacy, Universitas Gadjah Mada, 2016)
Hydrochlorothiazide is commonly used as first-line antihypertensive drugs. Hydrochlorothiazide is available in tablet dosage forms which has disadvantages such as taking long time to be absorbed, low bioavailability, and inconvenience for geriatric patients. Fast Disintegrating Tablet (FDT) is an alternative dosage form that can overcome the disadvantages of conventional tablets. This study aims to determine the effect of combination of Pearlitol® 400DC and croscarmellose sodium on the physical properties of FDT hydrochlorothiazide. Five runs of FDT hydrochlorothiazide are made using direct compression method, with the combination of Pearlitol® 400 DC and croscarmellose sodium are Run 1 (70%: 2%), Run 2 (68%: 4%), Run 3 (66%: 6%), Run 4 (64% : 8%), and Run 5 (62%: 10%). Evaluations of the FDT physical properties include hardness, friability, disintegration time, wetting time, water absorption ratio, and drug dissolution. Results are analyzed using simplex lattice design method with Design-Expert® software to obtain the optimum formula. Results show that the combination of Pearlitol® 400DC and croscarmellose sodium take effects to the physical properties of FDT hydrochlorothiazide. Increasing proportion of Pearlitol® 400DC may improve wetting time and friability, meanwhile increasing proportion of croscarmellose sodium may increase hardness, water absorption ratio, disintegration time, and reducing drug dissolution.